Meaning of learning mathematic in linguistic contexts of Quechua and city dwellers - Holguin-Alvarez, Jhon A. (2019)
The learning of mathematics and its teaching are complex for the Peruvian student and teacher, especially in contexts marked by low economic conditions, in which quechua has already been forgotten due to its scarce practice. As a purpose, we propose to characterize the meanings of the learning and teaching of mathematics in quechua and Spanish, based on the qualitative - narrative approach, we assume a sample of 10 students and two quechua speakers and Spanish speakers of Huancavelica and Comas district (Lima). We use two instruments for the measurement of student learning, and a survey of pedagogical approach. The study allowed to conclude that the students of the Andean zones present more difficulties than the student in terms of numbering and problem solving. Teachers use management strategies, characterized by traditional methods of learning construction; However, the instructions of the learning session required by the Ministry of Education can be followed.